Day 2 Tue, April 26, 2022 2022
DOI: 10.2118/209376-ms
|View full text |Cite
|
Sign up to set email alerts
|

Interference Analysis in Reservoirs with Bottom-Water Drive During Water Injection Processes Through Subsurface Connectivity

Abstract: This work analyzes the feasibility of implementing water injection processes through subsurface connectivity between different formations through communicating wells, allowing the water to flow from a source aquifer to a depleted formation. It presents a 3-dimensional semi-analytical model for estimating water influx in reservoirs with bottom-water drive and analyzing interference between reservoirs when subsurface connectivity is carried out to supply energy from an aquifer. It applies to both finite and infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Based on the experimental results from Table 1, the following conclusions can be drawn [1]: The formation water of deep Yanchang formation has a high content of scaling anions (HCO 3 -) and scaling cations (Ca 2+ ). During the uplifting process in oil depletion, the reduction of 6 Geofluids temperature and pressure leads to a large trend of inorganic scaling (CaCO 3 ) [2].…”
Section: Composition Of Injection/formation Water Samplesmentioning
confidence: 91%
See 2 more Smart Citations
“…Based on the experimental results from Table 1, the following conclusions can be drawn [1]: The formation water of deep Yanchang formation has a high content of scaling anions (HCO 3 -) and scaling cations (Ca 2+ ). During the uplifting process in oil depletion, the reduction of 6 Geofluids temperature and pressure leads to a large trend of inorganic scaling (CaCO 3 ) [2].…”
Section: Composition Of Injection/formation Water Samplesmentioning
confidence: 91%
“…In addition, crystallized scales such as NaCl and KCl exist at all positions of the wellbore. According to the above analysis results, it can be concluded that the scaling characteristics of oil wells in the Huanjiang oilfield in different payzones are as follows [1] 7 Geofluids deposition scale, corrosion scale, and NaCl and KCl crystal scale [2]. The oil wells in the Yan'an group (Yan 6, Yan 7, Yan 8, Yan 9, and Yan 10) are mainly wax deposition scale and corrosion scale, and the calcium-based scale is greatly reduced compared with that in the Yanchang group.…”
Section: Composition Of Injection/formation Water Samplesmentioning
confidence: 95%
See 1 more Smart Citation